2019
DOI: 10.1021/acsomega.9b00639
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-Doped Dendritic Structure as a Phosphorescent Label for Bacteria in Two-Photon Excitation Microscopy

Abstract: Herein, we present a water-soluble dendritric Pt(II) complex as a phosphorescent label for bacterial cells. The dendritic moiety endows the Pt(II) complex with unique properties such as water solubility, shielding from quenching by dioxygen, and binding to bacterial surfaces. The new biosensor was employed for two-photon excitation microscopy, and the binding was confirmed by electron microscopy, which demonstrates that such hybrid arrays can provide orthogonal yet complementary readouts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Cyclometalated transition metal complexes have been extensively studied in the last decades, mainly due to the broad range of applications derived from their photophysical properties. The utilization of coordination compounds has shown promising results in the fields of bioimaging, optoelectronics, photodynamic therapy, , and optical sensors, , among many others. While there are numerous compounds reported with d 6 -configured ions presenting nearly octahedral geometries, such as Ir­(III) or Re­(I) complexes, , Pd­(II)- and Pt­(II)-derived species have also shown a particular collection of interesting features.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclometalated transition metal complexes have been extensively studied in the last decades, mainly due to the broad range of applications derived from their photophysical properties. The utilization of coordination compounds has shown promising results in the fields of bioimaging, optoelectronics, photodynamic therapy, , and optical sensors, , among many others. While there are numerous compounds reported with d 6 -configured ions presenting nearly octahedral geometries, such as Ir­(III) or Re­(I) complexes, , Pd­(II)- and Pt­(II)-derived species have also shown a particular collection of interesting features.…”
Section: Introductionmentioning
confidence: 99%
“…We have also lately shown that the variation of monodentate coligands with variable bulk, , degree of coplanarization, and atomic number can drastically influence the structural and photophysical properties of monomeric and aggregated molecular entities with Pt­(II) centers. Moreover, ancillary ligands with dendrimeric anchors enabled us to label planktonic bacteria with Pt­(II)-based phosphorescence, whereas the adsorption of Pt­(II) complexes with suitably substituted tridentate luminophores allowed us to decorate proteins and gel-forming nanoclays …”
Section: Introductionmentioning
confidence: 99%
“…1308,1309 Strassert, Vida, Perez-Inestrosa, and co-workers have developed a dendritic platinum(II) complex (706) for labeling bacteria. 1310 The terminal amino groups of the dendritic skeleton are critical to the binding of the complex to the anionic bacterial cell surface via hydrogen bonding and electrostatic interactions.…”
Section: Bacterial Envelopementioning
confidence: 99%